Chen's Inequality for CR-warped Products in Locally Metallic Riemannian Manifolds (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we study CR warped product submanifolds in locally metallic Riemannian manifolds. We provide several non-trivial examples of such submanifolds. We establish a sharp inequality known as Chen's inequality for the squared norm of the second fundamental form. We also discuss the equality case of Chen's inequality.
Keywords: Warped product; CR warped product; Metallic Riemannian structure; Golden structure; CR submanifold